PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN (STUDI PADA BUMN DI BURSA EFEK INDONESIA) - Tedi Rustendi (Jurusan Akuntansi Fakultas Ekonomi Universitas Siliwangi, 2018)
The aims of this resarch is to known the influence of good corporate governance on firm value. The study conducted on SOEs as emiten in Indonesia Stock Exchange - IDX as study’s partner of IICG. Data was collected by documents review on annual reports and IICG’s report of governance rating related respondents include other publication that relevan with objective of review. Data were analyzed based on non-parametric statistics by rank correlation of Kendall’s τ. The result of data analysis shows that the level of firm value not influenced by good corporate governance. In this case, external stakesholders at its capital market not used the information of governance as key material in decision making related their investment.